On-farm practices for the safe use of wastewater in urban and peri-urban horticulture - Food and Agriculture Organization of the United Nations (2019)
The world’s population is growing rapidly and concentrating in urban centres. This trend is particularly intense in developing countries, where an additional 2.1 billion people are expected to be living in cities by 2030. However, sanitation coverage (collection and treatment) is not keeping pace with urban growth and as a result most wastewater enters water courses untreated.